Russian Organized Corruption Networks and their International Trajectories - Cheloukhine, Serguei; Haberfeld, M.R.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Countries undergoing major social and legal transitions typically experience a light, but relatively insignificant, increase in crime. However, in the past decade, many transitional countries in Eastern Europe, and Russia in particular, have experienced a surge in criminal activities that came about through the collaboration of diverse players$1 (Bsuch as criminals, state officials, businesspersons, and law enforcement$1 (Binto organized networks aimed to obtain financial and economic gains. In this process, two interdependent tendencies have become apparent: the "economization" of organized crime and the increased organization of economic crime itself. Both trends have led to a fundamentally new phenomenon in Russia, the Organized Corruption Network (OCN), which is a symbiosis that is a direct result of corruption, organized crime and economic crime within the Yeltsin and the Putin times. Russian Organized Corruption Networks and their International Trajectories aims to investigate the new phenomenon of OCN. This book addresses the fundamental changes that have taken place in Russia in the last five to seven years, including the increasing crime in the economy and the shift of power from organized crime/ mafia-like organizations to the Organized Corruption Networks.s
Keywords: Social sciences; Criminology; Political science; Social Sciences; Criminology & Criminal Justice; Political Science